Quick Evaluation Study on Fourteen (14) Major Development Programmes in Chatra District of Jharkhand State Affected by Left Wing Extremism (LWE) - Planning Commission (Planning Commission, 2011)
The state of Jharkhand became a functional reality on November 15, 2000 after almost sixty years of people's movements around the Jharkhandi identity. Located on Chhota Nagpur plateau and Santhal Parganas, it has evergreen forests, rolling hills and rocky plateaus with many places of mystic beauty. It has been carved out of the relatively backward southern part of undivided Bihar, sharing borders with the states of Bihar to the north, Uttar Pradesh and Chhattisgarh to the west, Orissa to the south, and West Bengal to the east. The industrial city of Ranchi is its capital, while other major cities and industrial centers are Jamshedpur,Dhanbad, Bokaro, Sindri, Deoghar Hazaribagh and Gumla.
Programme Evaluation Organisation Planning Commission
Programme Evaluation Organisation Planning Commission